Dermoid cyst of an undescended intra-abdominal testis with torsion: A rare case report - R Senthilnathan; S Vivek (Wolters Kluwer Medknow Publications, 2016)
We report a case of dermoid cyst in an undescended intra-abdominal testis, which presented with torsion and gangrene.